Identification and characterization of Yersinia intermedia isolated from human feces. - Punsalang, A (1987)
Since May 1983, our laboratory has, upon request, cultured stools for Yersinia spp. by using direct plating on cefsulodin-irgasan-novobiocin agar and a 3-week cold enrichment procedure. We isolated bacteria identified as Y. intermedia from six adult patients. All isolates were recovered only by the cold enrichment procedure and misidentified as Y. enterocolitica by the API 20E system (Analytab Products, Plainview, N.Y.). Final identification was made on the basis of results obtained with conventional tube biochemical tests. The isolates were tested for the following characteristics associated with virulence in Y. enterocolitica: lack of pyrazinamidase activity, autoagglutinability, presence of a 40- to 50-megadalton plasmid, production of heat-stable enterotoxin, and mouse lethality. All isolates tested had pyrazinamidase activity, and none were autoagglutinable. However, one isolate possessed a 40-megadalton plasmid. None produced enterotoxin or were lethal for mice. Review of the medical histories of the patients revealed that four of the six had diarrhea; however, none had disease typical of that caused by Y. enterocolitica. Our data confirmed the limited pathogenic potential of Y. intermedia and suggested that its isolation was without clinical significance in our patients. Conventional biochemical tests were required for reliable identification of Y. intermedia.